Analisis Prediksi Kebangkrutan Menggunakan Metode Altman Z-Score Pada PT. Sri Rejeki Isman Tbk Tahun 2013-2022 - Ita Adinda Pratika; Dina Pujiharti; Alisa Nurul Azka; Hanifah Hanifah; Nayla Audrey Aislinn; Nadila Aulia; Gunardi Gunardi; Linna Ismawati (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
The Altman Z-Score method is used in this research to determine the level of bankruptcy of PT. Sri Rejeki Isman Tbk from 2013 to 2022. Secondary data used in this research is in the form of company financial reports. In this research the data source was obtained from the financial reports of PT. Sri Rejeki Isman Tbk is listed on the Indonesia Stock Exchange (BEI). The five variables used in the Altman Z-Score method are working capital/total assets (X1), retained earnings/total assets (X2), earnings before interest and taxes/total assets (X3), and sales/total assets (X5). The results of this research indicate that the Altman Z-Score method can be applied to predict the possibility of company bankruptcy. The results of this analysis show that PT. Sri Rejeki Isman Tbk is predicted to experience bankruptcy in 2021-2022. This is indicated by the Z-Score value being below 1.8, which means that financial difficulties are very large and the risk is high. In 2018-2020 the company is predicted to be prone to bankruptcy and is marked with a value of 1.81 < Z-Score < 2.99.